2011
DOI: 10.1111/j.1751-0813.2011.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the proportion of under‐reporting during the 2007 equine influenza outbreak in New South Wales, Australia

Abstract: During the 2007 equine influenza (EI) outbreak in Australia, there was no objective information about the possible under‐reporting of cases by horse owners either so that they would avoid movement restrictions or because of their inability to detect infection. This investigation aimed to estimate the proportion of under‐reporting during the outbreak based on the results of surveillance undertaken in conjunction with vaccination. The results provided improved estimates of morbidity during the outbreak and indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Despite an overall low level of under‐reporting of 1.2% during the outbreak and <1% in south Sydney, higher levels occurred in certain areas including northern NSW (Dhand and Sergeant, 2011). Under‐reporting associated with distrust may have occurred in this area because of negative experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an overall low level of under‐reporting of 1.2% during the outbreak and <1% in south Sydney, higher levels occurred in certain areas including northern NSW (Dhand and Sergeant, 2011). Under‐reporting associated with distrust may have occurred in this area because of negative experiences.…”
Section: Discussionmentioning
confidence: 99%
“…We also adjusted for a number of relevant confounders of the meteorological associations we aimed to estimate: vaccination status of horses on the premises, premises size (in terms of area and number of horses), whether premises were adjacent to another premises holding horses, and local human population density. A small misclassification bias is known to be present in the equine influenza dataset, due to under-reporting of infected premises by owners either attempting to avoid movement restrictions or who failed to detect infection [72] . A previous analysis found <1% under-reporting occurred in this region, suggesting that <13 infected premises were misclassified as uninfected [72] ; we considered this bias negligible.…”
Section: Discussionmentioning
confidence: 99%
“…A small misclassification bias is known to be present in the equine influenza dataset, due to under-reporting of infected premises by owners either attempting to avoid movement restrictions or who failed to detect infection [72] . A previous analysis found <1% under-reporting occurred in this region, suggesting that <13 infected premises were misclassified as uninfected [72] ; we considered this bias negligible.…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence at a statewide level in NSW has been described by Dhand and Sergeant 9 and at particular locations in both NSW and QLD 10,11 . A study evaluating the level of under‐reporting of EI infection that occurred in NSW found that although the under‐reporting proportion varied regionally, overall, horse owners responsibly reported the majority of cases of disease to the authorities 12 …”
Section: Clinical Aspectsmentioning
confidence: 99%